3D model generation of real-objects using depth and color information - Sakib, Alium Basir; Azam, Hasnat; Jui, Tonni Das; Akter, Fahima (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.